Imperative Duality of Music Teacher Technological Education - Drew X Coles; Cato Zane (Journal of the Association for Technology in Music Instruction, 2025)
Referencing the TPACK (Technological Pedagogical and Content Knowledge) framework articulated by Mishra and Koehler, this article explains the need for educators to acknowledge and educate themselves regarding different proficiency tracks within the world of music technological content knowledge. We argue that our concept of “Imperative Duality” elaborates upon, and works to balance, the three elements of the TPACK framework: content knowledge, technological expertise, and pedagogical skills. With imperative duality, we explore the idea that educators must possess both content and technological knowledge to facilitate effective and comprehensive music tech instruction. This article also explores some music technology content and technological knowledge examples, expanding upon the benefits and limitations of each, so that we can better understand this need for different proficiency tracks within the field. We explore the importance of understanding the difference in capabilities between software options, and the importance of orienting these software options and a fluency with them within the TPACK framework. We argue that modern educators must have a working knowledge of the available music technology tools, both at the introductory levels and at more advanced levels, in order to both facilitate the classroom, as well as educate students on relevant technological content knowledge.
Keywords: music technology; music education; TPACK framework; technology education